Characteristics of Mexican Leather Footwear Industry and its International Trade Activity, Correlation of Productivity, and Competitiveness - Cisneros-Reyes, Y. D.; Rocha-Ibarra, J. E.; Arredondo-Hidalgo, M. G. (European Scientific Journal, ESJ, 2018)
This paper focuses on analyzing the globalization effect on the Mexican leather footwear industry at a firm-level. In this work, the analysis of competitiveness is done based on the definition given by the Organization for Economic Cooperation and Development (OECD). They defined it as â€˜a measure of a country’s advantage or disadvantage in selling its products in international marketâ€™. The productivity of the Mexican leather footwear industry was calculated using the Latin American-KLEMS Model that relates gross output to primary (Capital and Labor) and intermediate inputs (Energy, Other intermediate goods, and Services). Furthermore, firms were categorized considering the number of employees, the annual value of production, and the commercial diversification in order to calculate the correlation Pearson coefficient. Firstly, the results show that the correlation of production value with the number of exporting companies is bigger than the correlation of the importing companies. Secondly, that the correlation of Total Productivity Factor (TPF) to exports is strong (0.7028); and finally, that the correlation of Total Productivity Factor (TPF) to imports is also significant (0.6511).